Modification of pumice mineral and its use as additive for poly (lactic acid) based bio-composite materials - Dike, Ali Sinan (Afyon Kocatepe Üniversitesi)
In this study, pumice (P) mineral was treated with silane in order to increase the compatibility for poly(lactic acid) (PLA) which is a fully biodegradable polymer widely used in packaging and outdoor applications. Neat and treated P powders were compounded with PLA at the concentrations of 5, 10, 15 and 20 wt% by melt mixing process. Surface characteristics of P samples were examined using infrared spectroscopy. Mechanical, water uptake, melt-flow and morphological properties of prepared composites were investigated by tensile and impact tests, water absorption test, melt flow rate test (MFR) and scanning electron microscopy (SEM) technique, respectively. Mechanical test results revealed that the highest increase in tensile strength and modulus values was obtained for 15 wt% of silanized P containing composite which are found as 4.5% and 40% increase, respectively. Addition of silane-treated P into PLA resulted in an increase in impact strength of about 33% compared to samples containing that were not treated with silane with the same proportion of P. Impact strengths of composites increased with increasing P concentration. Silanized P filled composite gave slightly higher MFR values with respect to pristine P. Water absorption values of composites were found as about twofold higher than that of unfilled PLA. Composites containing silanized P exhibited lower water uptake values compared to untreated P samples because of the hydrophobic character of silicon containing surfaces. SEM micro-images of composites displayed that more homogeneous dispersion in PLA matrix was taken place for silane treated P particles than that of neat P stem from the increase of adhesion between P and PLA surfaces after silanization process.

Bu çalışmada, pomza (P) minerali, ambalaj ve dış ortam uygulamalarında sıkça kullanılan tamamen biyobozunur bir polimer olan poli (laktik asit) (PLA) ile uyumunu artırmak amacıyla silan ile muamele edilmiştir. Muamele edilen ve edilmeyen P tozları PLA ile eriyik karıştırma yöntemi ile ağırlıkça yüzde 5, 10, 15 ve 20 konsantrasyonlarında eklenmiştir. P numunelerinin yüzey özellikleri infrared spektrofotometre kullanılarak incelenmiştir. Hazırlanan kompozitlerin mekanik, su alma, erime-akış ve morfolojik özellikleri sırasıyla çekme ve darbe testleri, su emme testi, erime akış hızı testi (MFR) ve taramalı elektron mikroskopi (SEM) teknikleri ile araştırılmıştır. Mekanik test sonuçlarına göre, çekme dayanımı ve modülde en yüksek artışa %15 silanlanmış P içeren kompozitte sırasıyla %4,5 ve %40 artış ile rastlanmıştır. PLA içine silan ile muamele edilmiş P eklenmesi, silan ile muamele edilmemiş ve aynı oranda P içeren numuneler ile kıyasla darbe dayanımında %33 civarında artışa neden olmuştur. Kompozitlerin darbe dayanımları artan P konsantrasyonu ile artmıştır. Silanlanmış P eklenmiş kompozit, silanlanmamış P eklenmiş kompozite göre bir miktar yüksek MFR değeri vermiştir. Kompozitlerin su emme değerleri eklentisiz PLA’dan yaklaşık iki kat fazla olarak bulunmuştur. Silikon içeren yüzeylerin su sevmeyen özelliğinden dolayı silanlanmış P içeren kompozitler, modifiyesiz P ile kıyaslandığında daha düşük su emme değerleri sergilemiştir. Kompozitlerin SEM mikro-resimleri göstermektedir ki; silanlama işleminden sonra P ile PLA arasında yapışma arttığı için silan ile muamele edilmiş P parçacıklarında edilmeyenlere göre daha homojen dağılım gerçekleşmiştir
Türk pomza mineralinin modifikasyonu ve poli (laktik asit) bazlı biyo-kompozit malzemelerinde eklenti olarak kullanımı
Keywords: Pumice; Poly (lactic acid); Bio-composites; Extrusion; Polymer composites; Pomza; Poli (laktik asit); Biyo-kompozitler; Ekstrüzyon; Polimer kompozitler